Health for all: Primary care facility localization in Lesotho using qualitative research and GIS - Mariam A. Mostafa; Joy Oluwaseun Ogunmuyiwa; Kathryne Appleby Tenney; Sai Lone Tip; CarlosO. Zegarra Zamalloa; Jeffrey C. Blossom; Tlebere Mpo (Global Transitions)
Background: Lesotho has made significant strides towards universal health coverage and yet a significant proportion of the population has difficulty accessing health care services due to mountainous terrain and long travel times to nearest health facility. There have been previous studies that utilized Geographical Information Systems (GIS) to assess access to healthcare and to identify optimal locations for placement of new health facilities, though never in Lesotho. Methods: The authors employed a mixed-methods design. Qualitative research consisting of semi-structured interviews and focus group discussions was used to gain a deep understanding of the problem with access to healthcare and to allow for the perspectives of the people of Lesotho to guide decision-making about placement of new healthcare facilities. GIS analysis was done using ArcGIS Pro v. 2.3 software and modern satellite imagery to map current access to healthcare facilities and create site recommendations for new healthcare facilities. Results: Qualitative research revealed that walking was the primary mode of transport to healthcare facilities and that distance was the crucial barrier in limiting access to care. Decentralization in decision-making was identified as an important element in health policy decisions and study participants recommended placing health facilities centrally in large villages. GIS analysis identified that 77.7 % of the population was currently within 3-h walking distance to nearest health facility and that the addition of fifty new healthcare facilities would increase that proportion to 90.0 %. Conclusion: This study mapped current access to care in Lesotho in rural and urban areas. It also provided an objective strategy for identifying the location of new healthcare facilities while incorporating the voices of the people of Lesotho in the process. The findings can be used to assist policymakers, and the methodology can be employed in the allocation of other public-service facilities in different countries or regions.